(untitled) (Al-Qamar, 2026)
The contemporary world is facing a multi-dimensional ecological crisis, manifested through catastrophic floods, industrial waste, noise pollution, and the loss of biodiversity. This research investigates the ’Eco-Sunnah’ framework—environmental ethics derived from the Prophetic Seerah—as a sustainable solution to these modern challenges. The primary research problem addresses the moral and spiritual void in current environmental policies, which often fail to curb industrial excesses and resource mismanagement. The purpose of this study is to analyze how Prophetic teachings on cleanliness (Taharah), water conservation, and the ethical treatment of animals can be systematically adapted into a modern environmental governance model. Employing a descriptive and analytical methodology, the study draws upon the Qur’an and authentic Hadith to identify core principles such as stewardship (Khilafah), balance (Mizan), and the sanctity of all life. Findings indicate that the Prophetic models of Hima (protected zones) and Harim (buffer zones) provide practical strategies for flood management and urban planning. Furthermore, the study highlights that integrating the Sunnah of moderation (Iqtisad) is essential for mitigating industrial and noise pollution, which the Qur’an describes as Fasad (corruption on earth). The research contributes to the field by bridging the gap between spiritual ethics and technical implementation, offering a holistic ’Eco-Sunnah’ framework for global sustainability. It concludes that the adoption of these Prophetic principles is vital for fostering individual responsibility and institutional resilience in the face of rapid environmental change.